Structural, Dielectric and Enhanced Soft Magnetic Properties of Lithium (Li) Substituted Nickel Ferrite (Nife2o4)Nanoparticles - Casagrande-Denardin, J (Elsevier B.V., 2018)
Li-NiFe2O4 NPs have been prepared by a simple chemical co-precipitation method. The structural analysis of Li-NiFe2O4 nanoparticles with 2–31 nm demonstrates a face centered cubic spinel phase. The scanning electron microscopy and high resolution transmission electron microscopy images highlight moderate good nanocrystalline nature as compared to x = 0.4 concentration. The dielectric analysis shows that Li-NiFe2O4 NPs has a high dielectric constant at x = 0.2 concentration and then reduced with respect to annealing temperature and concentration. The magnetization curves demonstrate soft magnetic nature where, the saturation and remnant magnetization increases and then coercivity decreases due to increase of annealing temperature and concentration. © 2018 Elsevier B.V.